АПРОБАЦИЯ ТОС-ПОДХОДА ДЛЯ УПРАВЛЕНИЯ РИСКАМИ В ВОДОСНАБЖЕНИИ (World Science, 2019)
In this article is made the risk analysis in system of water supply of the plants of food. Approbation of Goldratt's Theory of Constraints allowed to mark out basic risk and to analyse shortcomings of the existing ways of disinfection. The perspective directions of minimization of risks in system of water supply of the enterprises of the food industry by use of reagents on the basis of PНMG-hcl are proved. This can real optimize work of all system of water supply of the enterprise of the food industry.